Relationship between the nutritional status of pregnant women and the incident of Low Birth Weight infant - Mardiaturrahmah Mardiaturrahmah; Anjarwati Anjarwati (Universitas 'Aisyiyah Yogyakarta, 2020)
The maternal mortality rate is 19,500 to 20,000 people every year or occurs every 26-27 minutes. The caus of maternal death is bleeding 30.5%, infection 22,5%, gestosis 17,5 and anesthesia 2%. The infant mortality rate is around 10,000 to 280,000 per 18-20 minutes. The cause of infant mortality is due to Low Birth Weight (LBW) of 15/1000%. The infant mortality rate in Indonesia is still the highest problem in other ASEAN countries. The infant mortality rate in Indonesia from 2008 was around 248 per 100,000 live births. Basic Health Research (RISKESDA) 2013 shows there are still 10,2% of babies with LBW, which is less than 2,500 grams. Neonatal death because LBW is basically affected by the nutritional status of pregnant women. This study aims to determine the relationship between the nutritional status of pregnant women and the incidence of LBW. This quantitative research uses a case control approach using a retrospective approach. The population in this study were mothers who had given birth to babies during the last two years (2016-2017). The sampling technique uses total sampling for control cases by using a ratio of 1: 1 for the case group of 40: 40 samples. Analysis using Chi Square with p value 0,000 (OR=3,500, CI 95%=2,313-5,296). There is a relationship between nutritional status of pregnant women and the incidence of LBW. Health Technology Assessment (HTA) which can seek 1000 first day of life can be a breakthrough in assessing and providing interventions of nutrition in families, especially in pregnant women.